(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Traditionally, two possible genitive singular markers in Celtiberian consonant stems have been identified: *-os and *-es. However, a review of the nominal inflection data in Celtiberian challenges this distribution. This study will argue that *-os is the more likely genitive singular ending and that instances suggesting allomorphism in the athematic genitive singular of consonant stems are unreliable.